TEKNIK PEMBENIHAN IKAN MAS (Cyprinus carpio) DI UPTD BALAI BENIH IKAN (BBI) CIMAJA, KABUPATEN SUKABUMI, JAWA BARAT - Mayapada Fajarwati; Yuli Andriani (Program Studi Budidaya Perairan Universitas Mataram, 2022)
Carp (Cyprinus carpio) is a widely cultivated consumable fish because of its high demand. This fieldwork practice aims to find out specifically about the hatchery techniques of carp. This fieldwork practice activity will be held on June 27-July 27, 2022 at the UPTD Balai Benih Ikan Cimaja Sukabumi. The data collection methods used are active participation, observation, and interviews. The data analysis used is descriptive. Carp hatchery activities start with brood rearing, selection of mature gonad broodstock, spawning, nursery, and water quality management. Spawning of carp is carried out naturally using 30 males and 6 females. The sex ratio of females and males was 5:1. The results of the number of fertilized eggs are around 70,535 eggs with a fertilization rate of 73.45%. The number of eggs that hatched was about 57,831 with a hatching rate of 81.98%. The number of seeds at the end of rearing was 40,521 seeds with a carp seed survival rate of 70.07%.